Work Analysis of Wire Handling Process Using Work Sampling Method and Standard Time Determination - Ayu Nurul Haryudiniarti; Widya Putri (Journal of Global Engineering Research and Science, 2022)
Productivity is one of the main factors in the company where productivity will affect the production output. This research was conducted on the wire handling process and the method used was work sampling and standard time determination, where previously statistical calculations were carried out to see the uniformity of the data and also the adequacy of the data. The method used in this study is the work sampling method, where time data sampling is done using a table of random numbers. In addition, standard time calculations are also carried out. The results obtained are productive activities as many as 160 out of 200 observations or by 80% and non-productive activities by 40 out of 200 observations or by 20%. Statistical testing for data uniformity shows that the observation data from the first day to the fifth day are (1) 0.80 (2) 0.80 (3) 0.825 (4) 0.80 (5) 0.775 still within the upper control limit and the lower control limit, which are 1.1 respectively. and 0.5. Sampling of the work that has been done can be concluded that with a 95% confidence level the percentage of working time that can be used productively by workers is 80% with a conclusion error rate of 10%. The standard time calculation obtained is 125.12 minutes for the wire handling process where this can still be improved if the operator is given training.